THE IMPORTANCE OF AN INTEGRATIVE APPROACH IN NATIVE LANGUAGE AND LITERATURE LESSONS - Boboyev Yusuf Beknazarovich (American Journals, 2023)
The importance of an integrative approach in native language and literature lessons " is an article on the benefits of introducing an integrative approach to teaching native language and literature. The article explains that by mastering various topics and skills, students can enrich their knowledge base, improve their analytical and critical thinking skills. Finally, the article argues that an integrative approach helps students develop important communication and digital literacy skills needed in the 21st century workforce. By incorporating digital technology into the lesson plan, students will be able to better understand and use different media to support their communication and creativity. In general, the article argues that an integrative approach is a powerful tool for growing comprehensive and deep understanding of native language and literature lessons.
Keywords: integration, integrative approach, Method, Research, Interdisciplinary communication, new technologies